2021
DOI: 10.4018/jeco.292474
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interconnections Between E-CRM, Customer Experience, Customer Satisfaction and Customer Loyalty

Abstract: This study examines the impact of electronic customer relationship management (E-CRM) on customer loyalty through the mediating effects of customer experience and customer satisfaction in the context of the banking industry. Customer experience and customer satisfaction are considered to be pre-requisite tools for improving and enhancing long-lasting relationships with customers. The study has adopted Stimulus-Organism-Response (S-O-R) model as theoretical support to examine the relationships. To achieve the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
1
16
1
1
Order By: Relevance
“…The result also highlights the significance of a dynamic capacity view (DCV). The association between customer relationship management and innovation capabilities has minimal empirical support (Migdadi, 2020), but it is well recognized that these two factors are related to other outcomes, customer satisfaction (Nguyen et al, 2020), performance (Alawiyah & Humairoh, 2017), customer loyalty (Mokha & Kumar, 2022), and commitment (Fauziyyah & Khaunsna, 2022). In view of the current study, which reveals the role of innovation capability in customer relationship management and SME performance, the need to create new products, markets, and processes are important factors that determine the creativity and innovation of an entrepreneur (Gontur, Davireng & Gadi, 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The result also highlights the significance of a dynamic capacity view (DCV). The association between customer relationship management and innovation capabilities has minimal empirical support (Migdadi, 2020), but it is well recognized that these two factors are related to other outcomes, customer satisfaction (Nguyen et al, 2020), performance (Alawiyah & Humairoh, 2017), customer loyalty (Mokha & Kumar, 2022), and commitment (Fauziyyah & Khaunsna, 2022). In view of the current study, which reveals the role of innovation capability in customer relationship management and SME performance, the need to create new products, markets, and processes are important factors that determine the creativity and innovation of an entrepreneur (Gontur, Davireng & Gadi, 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…A positive experience will increase CL and CE and motivate them to utilize the business' services again, while a negative one will make them switch to a rival. The results demonstrated that CE is significantly impacted by CX [39].…”
Section: Customer Experience (Cx)mentioning
confidence: 92%
“…However, in this modern era of banking where customers are needed for competitive edge , there is need to understand and enhance customer experience. (Kumar et al 2021;Garzaro et al 2020;Loureiro & Ferreira, 2017;Chahal & Dutta, 2015;Liljander & Strandvik, 1997), and loyalty (Mokha & Kumar, 2022;Mascarenhas et al 2006). Andaleeb et al (2016) ascertained banks can benefit profitably when they enhance customer experience.…”
Section: Customer Experiencementioning
confidence: 99%